Порівняльна гепатопротекторна ефективність флаванвмісних антидисбіотичних засобів у щурів з токсичним гепатитом - Васюк, В.Л.; Фурдичко, А.І. (Актуальні проблеми транспортної медицини, 2017)
Досліджені антидисбіотичні та гепатопротекторні властивості двох нових засобів: леквін (лецитин+кверцетин+цитрат кальцію) і лекасил (лецитин+макуха розторопші+цитрат кальцію) в порівнянні з препаратом квертулін (кверцетин+інулін+цитрат кальцію). Встановлено, що нові препарати більш ефективні ніж препарат порівняння. Исследованы антидисбиотические и гепатопротекторные свойства двух новых препаратов: леквин (лецитин+кверцетин+инулин+цитрат кальция) и лекасил (лецитин+жмых расторопши+цитрат кальция) в сравнении с препаратом квертулин (кверцетин+инулин+цитрат кальция). Установлено, что новые препараты более эффективны, чем препарат сравнения. The aim: To determine hepatoprotective activity of 3 flavanic antidysbiotic means (quertulin, lequin and lekasil).
The materials and methods: Quertulin (quercetin+inuline+citrate Ca), lequin (lecithin+quertulin) and lecasil (lecithin+oil cake Silybum marianum+citrate Ca) were used in dose 300 mg/kg per os in the rats wits hydrazin sulphate hepatitis. The experiment was 15 days. The markers of inflammation (the content MDA and the activity elastase) were determined in liver. The hepatitis markers (the content bilirubine, the activity ALT and activity alcaline phosphatase) were determined in serum.
The findings: The levels of the markers of inflammation raised in liver of rats with hepatitis, but after flavance means introducing they decreased. The levels of liver markers in serum raised in rats with hepatitis, but they decreased after flavanic means introducing. The lequin and lecasil were more active than quertulin.
The conclusion: The were flavanic means lequin and lecasil has antidysbiotic and hepatoprotective effectiveness.